Effects of Financial Accounting Theories on Accounting Practice in Sierra Leone - Conteh, Abdul; Kaira, Lamin (Formosa Journal of Multidisciplinary Research, 2024)
The article acknowledges the current practice of accounting, standard-setting process, contributes significantly in developing accounting principles than academic research, and principles of accounting are not entirely the product of academic study. A crucial academic concern is therefore how theory of accounting and research contribute to developed accounting principles. The paper discusses normative and descriptive (contemporary positivistic). Data were mainly collected mainly from primary source through questionnaire were issue to participants of 70 Accountant staff of Ministry of Finance and other financial institutions in Sierra Leone and only 55 of the questionnaires were received and processed. The modifications are advantageous for accounting enable a range of research philosophies that will elevate the standing accounting theory and perhaps accounting research. As a method of tracking and remotely monitoring the progress of economic activity, accounting appears to be a historical relic, generating economic impacts. Since accounting ideas have roots, they are no longer neutral. In this regard, it would be more like a slowly emerging structure infused with cultural influences, social unrest, and political issues and decisions. Responses were analysed using descriptive statistics, utilizing the Statistical Package for Social Science (SPSS statistic 26) and values of the responses have to be analysed in all cases to facilitate further discussions.